2020
DOI: 10.3390/jrfm13110291
|View full text |Cite
|
Sign up to set email alerts
|

Global FDI Inflow and Its Implication across Economic Income Groups

Abstract: Foreign direct investment (FDI) as a driver of growth is important in today’s globalized economy. It is extremely difficult for economies to grow sustainably without economic interactions outside their borders. However, there has been a debate on the impact of FDI inflow on economic expansion. Hence, this study investigated the influence of FDI on economic growth for a selection of 200 economies around the world for the period 1990–2018. We subdivided the sample into World Bank income group clusters to aid com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Results from both the Fixed Effect (FE) and Random Effect (RE) show that FDI has a significantly positive effect on growth in all the regions at 5% significance level, except for RE in Southern Africa with 10% significance level. As earlier indicated, FDI leads to the transfer of technology and resultant productivity from foreign countries to host countries, thereby increasing the productive capacity of the host countries as justified by the positive coefficient of FDI for the regions in Sub-Saharan Africa as supported by Joshua et al (2020c) Consequently, the R-squared statistic is high and does suggest that the model contains variables that explain the changes in the dependent variable real per capita income.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Results from both the Fixed Effect (FE) and Random Effect (RE) show that FDI has a significantly positive effect on growth in all the regions at 5% significance level, except for RE in Southern Africa with 10% significance level. As earlier indicated, FDI leads to the transfer of technology and resultant productivity from foreign countries to host countries, thereby increasing the productive capacity of the host countries as justified by the positive coefficient of FDI for the regions in Sub-Saharan Africa as supported by Joshua et al (2020c) Consequently, the R-squared statistic is high and does suggest that the model contains variables that explain the changes in the dependent variable real per capita income.…”
Section: Resultsmentioning
confidence: 89%
“…A similar study for Asian economies by Goh et al 2017 showed the influence of FDI inflows in the region is uncertain. Similarly, Joshua et al (2020c) revealed that external debt is a key determinant of global economic growth. Joshua et al (2020c) indicated that external debt exhibits a positive and significant impact on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…He studied a new methodology for the Flows of Financial Capital in the form of Foreign Aid from Donor Countries, besides, this methodology allows (Cognitive Modeling) learning and proving the Impact of Financial Capital, Foreign Aid and other factors that affect the Economic Growth of the country [43,44].…”
Section: Literature Reviewmentioning
confidence: 99%